Pengembangan Modul Bimbingan dan Konseling yang dapat digunakan Guru Bimbingan dan Konseling atau Konselor untuk Peningkatkan Self-Esteem (Penghargaan terhadap Diri Sendiri) Siswa - Rhepon, Sarleni; Nirwana, Herman; Marjohan, Marjohan (Konselor, 2016)
The purpose of this research was to reveal whether the Guidance and Counseling module designed for increasing the students’ self-esteem had been proper in terms of content and appearance, and to describe the usability level of the Guidance and Counseling module to increase the students’ self-esteem. This research applied ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The subjects of the research consisted of 6 experts to see the properness of the module and 3 Guidance and Counseling teachers to see the usability level of the module. This research was conducted by trying out the product and through Focus Group Discussion (FGD). The data of the research were analyzed by using descriptive statistic analysis and inferensial statistic. Based on these results, in general, the prototype of Guidance and Counseling module designed for increasing the students’ self-esteem had been proper and could be used by the Guidance and Counseling teachers to increase the students’ self-esteem.